Impact of tourism on regional economic growth: A global value chain perspective - Anyu Liu (Asian Development Bank (ADB), 2022)
In the globalization era, many products in the tourism industry are imported from other economies; whereas other products may be exported as intermediates to other economies. Researchers have assessed the economic impact of tourism for more than 40 years, but have shed little light on the economic impact on economies in the global value chain. To fill this gap, this analysis used the multiregional input-output table with 35 industries and 63 economies to comprehensively examine the economic contribution of tourism to Thailand as well as to the global economy. Findings suggest that tourism in Thailand generates significant economic impact on output and value added. The industry has stronger intra-spillover and linkage with domestic industries, particularly downstream industries, and weaker connections with industries in other economies in the global supply chain. The multiregional input-output model also reveals that it can measure the export performance of the industry more accurately than the traditional input-output model. Findings generate comprehensive empirical results for destinations and regional organizations to more accurately strategize tourism or regional tourism development plans.
Keywords: R15; Z32; 330; multiregional input-output model; global value chain; economic impact; tourism development